Vsesoiuznaia chitatel'skaia konferentsiia . Vsesoiuznaia chitatel'skaia konferentsiia . All-Union Readers Conference . Всесоюзная читательская конференция - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Meeting with the editorial board and writers of the magazine "Novyi mir." Featured in the program: Aitmatov, Chinghiz Torekulovich (Writer); Zalygin, Sergei Pavlovich (Chief Editor of magazine "Novyi mir" [New World]); Nikolaeva, Olesia (Poet) Встреча с редколлегий и авторами журнала "Новый мир". В программе участвуют: Айтматов, Чингиз Торекулович (Писатель); Залыгин, Сергей Павлович (Главный редактор журнала "Новый мир"); Николаева, Олеся (Поэтесса)